Investigating the Causal Relationship Between Epistemological Beliefs and Mathematics Anxiety with the Mediating Role of Academic Self-Efficacy in Female Upper Secondary School Students in Fereydunkenar - Babai, Leila; Sadeghi, Jamal; Akbarnataj Shoob, Nabiollah; Mohammadzadeh Admalai, Rajabali; Khan Mohammadi, Arsalan (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to examine the causal relationship between epistemological beliefs and mathematics anxiety with the mediating role of academic self-efficacy among female upper secondary school students.Methods and Materials: This study employed a descriptive–correlational design using structural equation modeling (SEM). The statistical population consisted of all female upper secondary school students in Fereydunkenar during the 2024–2025 academic year, from whom 354 students were selected through appropriate sampling procedures. Data were collected using Schommer’s Epistemological Beliefs Questionnaire (1990), the Academic Self-Efficacy Scale developed by Jinks and Morgan (1999), and the Revised Mathematics Anxiety Rating Scale by Plake and Parker (1982). Prior to analysis, assumptions of normality and absence of multivariate outliers were examined and confirmed. Data were analyzed using SPSS version 27 and AMOS version 24. Direct and indirect effects were estimated within the proposed structural model, and statistical significance was evaluated at the .05 level.Findings: Structural equation modeling indicated that epistemological beliefs had a significant direct positive effect on mathematics anxiety (β = 0.56, p = .001) and a significant direct negative effect on academic self-efficacy (β = -0.58, p = .001). Academic self-efficacy demonstrated a significant direct negative effect on mathematics anxiety (β = -0.38, p = .001). Moreover, the indirect effect of epistemological beliefs on mathematics anxiety through academic self-efficacy was statistically significant (β = 0.22, p = .001), confirming the mediating role of academic self-efficacy in the structural model.Conclusion: The findings underscore the critical role of cognitive–motivational factors in explaining mathematics anxiety and suggest that naïve epistemological beliefs increase anxiety both directly and indirectly by diminishing students’ academic self-efficacy, highlighting the importance of targeting epistemological beliefs and strengthening self-efficacy in educational interventions.